A Tool Support for Web Applications Adaptation Using Navigation History - Firmenich, Sergio (2011)
Currently the Web is a platform for performing complex tasks which involve dealing with different Web applications. However users still have to face these tasks in a handcrafted way. In this paper we present a novel approach that combines concern-sensitive adaptation and navigation history to improve the user experience while performing a task. We have developed some simple though powerful tools for applying this approach to some typical tasks such as trip planning and house rental. We illustrate the paper with a simple though realistic case study and compare our work with others in the same field.